1987
DOI: 10.1002/bbpc.19870910615
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Reactions of CH3 2. H‐Abstraction from Alkanes

Abstract: Thc rate coefficients of the reactions CH, + C& -+ CH4 + C2Hs (1) and CH3 + CD4 .--t CD4 -+ CH3D + CD3 (2) were determined at high temperatures behind incident shock waves by time-resolved measurements of the absorption of the methyl radical at 216.5 nm. The resulting Arrhenius expressions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
3

Year Published

1989
1989
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 42 publications
5
27
3
Order By: Relevance
“…At high temperatures, the only inconsistent data are the rate constants of Møller et al 72 for CH 3 + ethane, obtained using optical absorption techniques for methyl radicals. These appear to be too large and are in poor agreement with the other data.…”
Section: Articlementioning
confidence: 93%
“…At high temperatures, the only inconsistent data are the rate constants of Møller et al 72 for CH 3 + ethane, obtained using optical absorption techniques for methyl radicals. These appear to be too large and are in poor agreement with the other data.…”
Section: Articlementioning
confidence: 93%
“…The following reaction steps are dominated by oxygen addition, to form oxygenated species like alcohols, aldehydes, ethers etc., and further decomposition steps like abstraction of H atoms or hydrocarbons. H-abstraction reactions of different hydrocarbons were the focus of several theoretical [5][6][7][8][9][10] and experimental studies [11][12][13][14][15][16][17][18]. Khaled et al have investigated the reactions of linear alkenes [11] and i-butene [12] with OH radicals in shock tubes and showed that the reaction rate coefficients are dependent on the chain length and the position of the double bond, that is, the constitutional isomer.…”
Section: Introductionmentioning
confidence: 99%
“…Manion et al [16] investigated H-abstraction reactions of n-alkanes by H and CH 3 radicals and showed a strong temperature dependence of the ratio between primary and secondary H-abstractions. The Habstraction by CH 3 radicals from ethane was the target of the investigations by Möller et al [17], while the decomposition of butane isomers by H radicals was investigated by Peukert et al [18] in a shock tube study.…”
Section: Introductionmentioning
confidence: 99%
“…5) together with the rate constants of the reactions mentioned (5, 15,45). The data for the reaction CH3 + CH4 have been calculated from preliminary measurements of CH3 + CD4 [13].…”
Section: Several Experimental Studies Have Been Devoted To the Kinetimentioning
confidence: 99%